EFEKTIFITAS STRATEGI PENANGANAN TERORISME DI ACEH MELALUI SISTEM PERTAHANAN RAKYAT - Ferga Abi Nurmansyah (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2021)
Being far from the center of government and the limited number of security forces, make Aceh very vulnerable to terrorism. In various religious and social communities, the people’s actually have an important role in spreading terrorism networks in Aceh. This study aims to analyze the effectiveness of counterterrorism strategies by involving the public defense system. This research was prepared using a qualitative explanatory method with a detailed description. Data obtained through secondary data from the previous researches and credible media. The results show that the People's Defense System can be implemented effectively because it is in line with the national defense system, namely total defense system. The people in Aceh are indirectly able to fill the void in the supervisory space that cannot be carried out by law enforcement officials. The strong influence of Islamic culture in Aceh can be used as a means to raise public awareness of the dangers of the of radicalism issue that leads to the terrorism.